Arsitektur Sistem Informasi Akademik Perguruan Tinggi Swasta Menggunakan EAP - Fatoni Fatoni; Edi Supratman; Darius Antoni (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Universities in Indonesia already have academic information systems. This university in developing its academic information system is carried out individually according to conditions and needs. Currently there are no guidelines in providing direction for the planning, development, implementation and service of academic information systems based on information and communication technology in universities. In addition to this, it is based on the planning and development of an academic information system which is what will be planned and developed and how its development guidelines are not yet available. The purpose of this study is to provide guidance in building academic information systems at private universities that can be applied in South Sumatra Province. This goal needs to be done because in general the academic information system business processes and services as well as the need for information in each university have in common namely the acceptance of new students, academic management and academic release. The result of the research is an academic information system architecture as a guideline in planning the development of an academic information system according to the conditions of private universities in South Sumatra Province. This study uses the EAP method with the steps of activities including planning initiation, business modeling and survey of current institutions, systems and technologies, data architecture and application architecture. The results of this study are a guide in building a system in the form of an academic information system architecture that can be applied to private universities in Indonesia especially South Sumatra Province.This study uses the EAP / Enterprise Architecture Planning method with activity steps including planning initiation, business modeling and institutional surveys, current systems and technology, data architecture and application architecture.